Electroconvulsive Therapy: The Impact of a Brief Educational Intervention on Public Knowledge and Attitudes. (January 2018) - Hoffman, Gretchen A.; McLellan, Jacee; Hoogendoorn, Vanessa; Beck, Andrew W.
The safety and efficacy of electroconvulsive therapy (ECT) are well established, yet efforts to educate the public about ECT advancements are lagging. The purpose of this study was to experimentally examine the impact of a brief educational intervention on public knowledge of, and attitudes toward, ECT. Participants ( n  = 91) from a private liberal arts university in the upper Midwestern region of the United States were randomly assigned to either an educational intervention or a control group. The educational intervention group read a brief informational pamphlet about ECT. Both groups completed a 24-item ECT knowledge and attitude measure. Participants who read the ECT pamphlet demonstrated significantly higher levels of ECT knowledge and reported more favorable attitudes toward ECT than did the control group. Furthermore, knowledge of ECT significantly predicted attitudes toward the treatment. Educating the public about available medical treatments not only facilitates help-seeking behavior among prospective patients and their families, but also it hallmarks the informed consent process once help is sought.